Spatial separation of ions of a given mass range in the demo-imitation separator at the first turn of ionic trajectory - Katrechko, V.V.; Yuferov, V.B.; Ilichova, V.O.; Khizhnyak, S.N. (Вопросы атомной науки и техники, 2021)
Plasma methods, where only electricity is required, are an alternative to the PUREX process used in industry for spent nuclear fuel reprocessing. It is considered the possibility of filtering out the target ions (М = 232…277) to the collector at the first turn of the ion trajectory in the plasma mass filter, which is currently being developed, that is achieved by specifying certain parameters (amplitude and frequency) for a variable component of a radial electric field. This approach significantly reduces the thermal load onto deposition surface of target ions. Альтернативою пьюрекс-процесу, який застосовується в промисловості при переробці відпрацьованого ядерного палива, є плазмові технології, де потрібна тільки електроенергія. Розглянута можливість виходу цільових іонів (М = 232...277) на колектор на першому витку іонної траєкторії в плазмовому фільтрі мас, котрий зараз розробляється, що досягається при завданні певних параметрів (амплітуди та частоти) змінної компоненти радіального електричного поля. При такому підході значно зменшується теплове навантаження на поверхню осадження цільових іонів. Альтернативой пьюрекс-процесса, который применяется в промышленности при переработке отработавшего ядерного топлива, являются плазменные технологии, где требуется только электроэнергия. Рассмотрена возможность выхода целевых ионов (М = 232...277) на коллектор на первом витке ионной траектории в плазменном фильтре масс, который в настоящее время разрабатывается, что достигается при задании определенных параметров (амплитуды и частоты) переменной составляющей радиального электрического поля. При таком подходе существенно уменьшается тепловая нагрузка на поверхность осаждения целевых ионов.